2022
DOI: 10.31875/2410-2199.2022.09.01
|View full text |Cite
|
Sign up to set email alerts
|

PVP-Assisted Hydrothermal Synthesis of Bi2O2Se Nanosheets for Self-Powered Photodetector

Abstract: Bi2O2Se nanosheets were successfully synthesized via a facile one-step PVP-assisted hydrothermal process for the first time. Corresponding characterizations, such as XRD, XPS, SEM and TEM, were carried out to investigate the formation of the products on the amount of PVP in the reaction system. Results revealed that the single-crystalline Bi2O2Se nanosheets with small mean lateral size of 176.3 nm were obtained when the amount of PVP is 0.75 g. Single-crystalline Bi2O2Se nanosheets self-powered photodetector e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 21 publications
(12 reference statements)
0
3
0
Order By: Relevance
“…Compared to the other inorganic materials including the bismuth-based and other well-investigated 2D material-based PEC-type photodetectors, the Bi 13 S 18 I 2 PEC-type photodetector exhibited much superior photodetection performance in terms of responsivity and response time (Table S2). , One possibility for the excellent performance might be derived from the high quality, including high purity, continuous surface morphology, and relatively strong adhesion of the films on the substrate, of Bi 13 S 18 I 2 thin films synthesized by mist CVD.…”
Section: Resultsmentioning
confidence: 99%
“…Compared to the other inorganic materials including the bismuth-based and other well-investigated 2D material-based PEC-type photodetectors, the Bi 13 S 18 I 2 PEC-type photodetector exhibited much superior photodetection performance in terms of responsivity and response time (Table S2). , One possibility for the excellent performance might be derived from the high quality, including high purity, continuous surface morphology, and relatively strong adhesion of the films on the substrate, of Bi 13 S 18 I 2 thin films synthesized by mist CVD.…”
Section: Resultsmentioning
confidence: 99%
“…The photodetection performance for OV-Bi 4 O 5 I 2 PEC-type photodetector was much better than those of other bismuth-based PEC-type photodetectors and comparable to the well-investigated inorganic materials-based PEC-type photodetectors (Figure 4g and Table 1). [3,5,11,[44][45][46][47][48][49][50][51][52][53][54][55][56][57] These results strongly suggested that OV-Bi 4 O 5 I 2 PEC-type photodetector is a promis-ing nanodevice suitable for various applications, like optical imaging, optical communication, and biomedical detection.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, bismuth binary and mixed-anion compounds have been gradually used for the construction of PEC-type photodetectors. 79,147,149,[217][218][219][220][221][222][223][224] The photodetection performance of bismuth binary and mixed-anion compound-based PEC-type photodetectors is summarized in Table 5. Remarkably, these photodetectors demonstrate a performance that is comparable to, and sometimes even superior to, the well-studied compound-based PEC-type photodetectors…”
Section: Dalton Transactions Perspectivementioning
confidence: 99%